On surface pressure fluctuations in turbulent boundary layers - Lilley, G. M. (College of Aeronautics, 1960)
Existing work on the pressure fluctuations in turbulent shear flaws is briefly reviewed with special reference to the problem of wall turbulence. An approximate theory for the pressure fluctuations on the wall under both a turbulent boundary layer and a wall jet is given and indicates in the latter case an intensity many times that corresponding to the flow over a flat plate at zero pressure gradient, as typified by measurements on the wall of a wind tunnel. Experiments on a wall jet confirm these predictions and details of the few preliminary data are presented. The results from the wall jet suggest that the intensity of the pressure fluctuations in the regions of adverse pressure gradient, on wings and bodies approaching and beyond separation will be higher than in regions of zero pressure gradient. Appendices are included which deal with the necessary extensions to the analysis to fit the velocity correlation functions as measured by Grant (1958), the effects of time delay and eddy convection.